DETERMINANTS OF FOOD SECURITY AMONG RURAL HOUSEHOLDS IN KENYA - Njoroge, Jacqeline Wanjiku; Murunga, James; Karau, James (International Journal of Social Sciences and Information Technology, 2024)
In Kenya, ensuring food security among rural households is pivotal for sustainable development and poverty alleviation. With about 71 percent of Kenya’s population living in the rural areas and agriculture being the main economic activity, 36 percent of the rural population is experiencing food poverty. The main focus for this study is to establish the determinants of food security among rural households in Kenya. The study is grounded on the Engel Curve theory. Data for this study is obtained from the Kenya Integrated Household Budget Survey (KIHBS) 2015/16, covering 13,092 rural households. Logistic regression estimation technique was employed to meet the study objectives. The findings reveal that education status of the household head, access to credit, household size and income are significant determinants of food security among rural households in Kenya. The education status of the household head, access to credit and income have positive effects on household’s food security while household size has a negative effect on household food security. The study recommends that credit facilities be made accessible for rural farmers to help them expand both on farm and off farm operations, thus enhancing household food security. The government should also prioritize expanding education access in rural areas and implement policies to boost household income by supporting agricultural value chains and improving market access. Additionally, policy measures focused on family planning should receive adequate attention to reduce household sizes to a level that household heads can manage effectively.
Keywords: Food Security; Food Insecurity; Kenya Integrated Household Budget Survey; Rural Households